PRACTICE OF BUYING AND SELLING BARTERING VEGETABLES WITH KITCHEN SPICES IN ISLAMIC ECONOMY - Eny Widiaty; Hendri Saleh (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2023)
The background of this article is that several farmers and planters in Dasan Bawak Hamlet, Lelede Village, made barter transactions which must be further studied whether these transactions are in accordance with religious law. The purpose of this thesis is to find out how the practice of buying and selling goods for goods in Dusun Dasan Bawak is carried out and to find out how Islamic law analyzes the practice of bartering that occurs in Dusun Dasan Bawak. The results of this study concluded that the practice of buying and selling goods for goods (barter) that occurred in Dasan Bawak Hamlet, between the owner of the goods and the buyer did not hand over the goods directly and there was no clarity and agreement between the two in the type, quantity and size of the goods to be purchased. there will be bartering and there will be no time constraints on both parties and there is a sense of loss that is often experienced after bartering. One of the causes is that the number and type of goods that have been bartered do not match the size of the goods that have been taken by the buyer from the seller's field, so that the seller feels a loss due to the discrepancy. As for buyers who will sell these goods to the market, sometimes these goods do not sell well so that buyers who will sell goods feel at a loss because the goods must still be paid for with other goods, and also due to ambiguity, loss and a bit of compulsion. This problem is the cause of illegal barter buying and selling transactions that occurred in Dasan Bawak Hamlet because they did not fulfill some of the pillars and conditions of buying and sellingeven though there was a mutual feeling of letting go between the two until now this transaction is still being carried out to help meet the needs of life and the world of marriage. for mothers in Dasan Bawak Hamlet.